PHYSICO-CHEMICAL PARAMETERS OF WINE MATERIALS FROM LOCAL GRAPE - Sh.N.Ismatova; Sh.Zh.Yuldasheva; O.I.Sultonova (Western European Studies, 2024)
the article analyzes the biochemical composition of various grape varieties grown in the Bukhara region, determining the sugar content, acidity of grape varieties, ethyl alcohol in wine materials, volatile acids, SO2. It has been analyzed that these physicochemical indicators meet the requirements of GOST
Keywords: grape varieties; Saperavi; Kaberne; Hindogni